Virudh Ahara in Ayurveda: Insights into Its Role in Preventive Health Care - Kumar, Pawan; Rani , Seema (International Research Journal of Ayurveda & Yoga, 2025)
Background: Virudh Ahara (incompatible food combinations) represents a fundamental concept in Ayurveda, describing foods that disrupt physiological homeostasis. With rising lifestyle diseases, understanding Virudh Ahara has become increasingly relevant for preventive health care. Materials of Review: Classical Ayurvedic texts (Charaka Samhita, Sushruta Samhita, Ashtanga Hridaya) and contemporary research from PubMed, Google Scholar, and AYUSH databases. Methods of Review: Systematic literature review using keywords “Virudh Ahara,” “incompatible foods,” “lifestyle diseases” for studies published 2000–2024. Type of Review: Narrative review combining classical knowledge with contemporary evidence. Results of Review: Analysis revealed Virudh Ahara contributes to lifestyle diseases through Agni dysfunction, Ama formation, and Dosha imbalance. Modern dietary habits align with classical incompatibility categories. Conclusion: Virudh Ahara provides a critical framework for understanding diet-related pathogenesis and serves as a valuable tool for preventive healthcare strategies.